THE INFLUENCE OF SELF-CONTROL AND RELIGIOSITY ON THE CONSUMPTIVE BEHAVIOUR OF GENERATION Z SOCIETY IN BEKASI CITY. - Muhammad Luthfi Hasan; Ina, Ratnasari (Universitas Indo Global Mandiri Palembang, 2025)
Abstract Objective: This study aims to determine, analyse and explain whether self-control and religiosity can influence consumptive behaviour in generation Z society partially or simultaneously. Design/Methods/Approach: Research Methods Using a Quantitative Approach, Descriptive Analysis, which is a method used to describe and summarise data quantitatively. This technique is used to provide an overview of the data, so that it can be used to draw conclusions and make decisions. Using the literature review method is a description of the theories, findings and other research materials obtained from reference materials to serve as the basis for important studies. Findings: self-control and religiosity have a significant negative effect on the consumptive behaviour of generation Z people in Bekasi city partially or simultaneously. This means that the higher the level of self-control or religiosity, the lower the consumptive behaviour and vice versa, the lower the level of self-control or religiosity, the higher the level of consumptive behaviour Originality/Value: This study discusses the effect of self-control and religiosity on consumptive behaviour in the generation Z community in Bekasi city. Practical/Policy implication: This research is expected to help generation Z and related governments in controlling and controlling the consumptive behaviour of the younger generation or generation Z.